PRINCIPAL PERSONALITY COMPETENCE IN MANAGING WORK CULTURE AT MTS N JAMBI LUAR KOTA, KAB. MUARO JAMBI - Jamilah Jamilah; Munawaroh Munawaroh (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
Madrasah principals have so far been too focused on developing their own professionalism at work, by slightly ignoring the personality factor as an important part of the success of the teacher's work. This study aims to examine the personality competencies of madrasah principals and the influencing factors in managing work culture at MTs N Jambi Luar Kota. Research subjects were determined by purposive sampling technique. This study uses a qualitative approach with data collection methods, namely: observation, interviews and documentation. Data analysis includes data reduction, data presentation and verification/drawing conclusions. The results of this study indicate that the personality competence of the head of madrasa in managing work culture at MTs N Jambi Luar Kota of Muaro Jambi Regency has not been maximized because the attention and responsibility of the head of madrasa towards various management of work culture is still dominated by integrity, namely the value of discipline in work, besides the principal upholds an open attitude in its leadership both to teachers, staff, and users. Meanwhile, in self-development, self-control ability, and interests and talents as a leader do not appear to be actually carried out in managing and naming a professional and quality work culture. Other findings related to the influence of madrasah principals in managing work culture at MTs N Jambi Luar Kota are intensive communication with teachers and fostering teacher discipline by compiling work rules and giving warnings to teachers who have made mistakes. The conclusion of this study is that the aspect of personality competence in managing a productive work culture, the madrasa principal is not proactive in cultivating, familiarizing or managing work culture in MTs N Jambi Luar Kota